2014
DOI: 10.1186/s13089-014-0016-y
|View full text |Cite
|
Sign up to set email alerts
|

Current practice of lung ultrasonography (LUS) in the diagnosis of pneumothorax: a survey of physician sonographers in Germany

Abstract: BackgroundThe purpose of this study was to survey the current practice of the use of lung ultrasonography (LUS) in the diagnosis of pneumothorax.MethodsPhysician sonographers, accredited for diagnostic ultrasonography in surgery, anaesthesia and medicine were studied. Questions addressed the frequency of exposure to patients with suspected pneumothorax, frequency of LUS use, preferences regarding technical aspects of LUS examination, assessment of diagnostic accuracy of LUS and involvement in teaching.ResultsO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…But as pneumothorax is a known complication in 3-5% of cases after TBB [2], TUS is reliably useful to distinguish patients without a risk of post-procedural complications, helps simplifying the postprocedural monitoring and avoids unnecessary X-ray-exposition. This is clinically important as pneumothorax exclusion as a main indication is still not widespread in Germany [14].…”
Section: Discussionmentioning
confidence: 99%
“…But as pneumothorax is a known complication in 3-5% of cases after TBB [2], TUS is reliably useful to distinguish patients without a risk of post-procedural complications, helps simplifying the postprocedural monitoring and avoids unnecessary X-ray-exposition. This is clinically important as pneumothorax exclusion as a main indication is still not widespread in Germany [14].…”
Section: Discussionmentioning
confidence: 99%
“…latter would have required us asking open questions. Those types of questions are difficult to analyse and interpret [12]. Our study may also be criticized for what might be considered a low response rate (26%) suggesting a degree of self-selection of participants.…”
Section: (9)mentioning
confidence: 85%
“…In infants with a pneumothorax, lung ultrasound can help determine the need for needle thoracostomy and chest tube drainage. 14,72,115 In 2019, a systematic review and meta-analysis showed that the overall specificity of lung ultrasound in diagnosing pneumothorax in neonates was 96.7% (95% confidence interval 88.3-99.6%). 14 Lung sliding is an important sign; its presence practically rules out pneumothorax.…”
Section: Evaluation For Pneumothoraxmentioning
confidence: 99%